2017
DOI: 10.1016/j.cps.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy and Nerve Compression Syndromes in Burns

Abstract: Peripheral neuropathy and nerve compression syndromes lead to substantial morbidity following burn injury. Patients present with pain, paresthesias, or weakness along a specific nerve distribution or experience generalized peripheral neuropathy. The symptoms may manifest at various times from within one week of hospitalization to many months after wound closure. While current treatments require surgical release of entrapped or compressed nerves, additional studies are necessary to develop therapies for periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 62 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…This could be attributed to the early recognition of fracture on an X-ray or clinical examination. Fracture is more evident in the primary survey and hence rarely missed [22].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the early recognition of fracture on an X-ray or clinical examination. Fracture is more evident in the primary survey and hence rarely missed [22].…”
Section: Discussionmentioning
confidence: 99%
“…Burn injury has been shown to contribute to several types of peripheral neuropathies associated with sensory dysfunction (Strong, Agarwal, Cederna, & Levi, ). Excessive peripheral nerve firing activity within scar tissue, peripheral nervous system (PNS) and CNS inflammation, loss of inhibitory regulation, and structural plasticity can contribute to chronic secondary complications associated with burn injury (Bijlard et al, ; Chang & Waxman, ; Guo et al, ; Shields et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuropathy is not well documented or recognized in burn patients; hence, it is probably frequently missed or overlooked in clinical settings [2]. An association between peripheral neuropathy and burn incidents has been established, which is varied widely [2,3], for example, 2% to 84% of burn patients, depending on different methodologies. Helm et al assessed 66 burn patients and reported neuromuscular problems in 29% of burn patients [4], while Gabriel et al reported the prevalence of 5% (18/370) Moreover, peripheral neuropathy has a serious effect on rehabilitation [5].…”
Section: Introductionmentioning
confidence: 99%